The Effect of Fashion Involvement, Shopping Lifestyle and Hedonic Shopping Value on Implement Buying of Fashion Products in The Shopee Application : (A Study of Students of The Faculty of Economics and Business, Islamic University of Lamongan) - Putri Dyah Pitaloka; Nurul Badriyah (International Journal of Economics and Management Research, 2024)
In this Digital era, Events occur in teenagers who do shopping activities for pleasure and are emotionally involved with the world of fashion and lifestyle that centers on shopping activities. This increases experiences such as pleasure, positive emotions and personal satisfaction so that they make purchases impulsively. This study was conducted to determine the Effect of Fashion Involvement, Shopping Lifestyle and Hedonic Shopping Value on Impluse Buying on Fashion Products on the Shopee application. This study uses a quantitative approach with a survey method. Samples were taken randomly from active Shopee users with certain criteria. Data were collected through a questionnaire that measured the variables that were studied, namely fashion involvement, shopping lifestyle, hedonic shopping value and impulse buying. Data analysis was carried out using multiple linear regression techniques to test the research hypothesis. The results showed that fashion involvement did not have a partial effect on impulse buying, shopping lifestyle and hedonic shopping value had a positive and significant effect on impulse buying on purchasing fashion products on the Shopee application.